2010
DOI: 10.1007/s12630-010-9328-y
|View full text |Cite
|
Sign up to set email alerts
|

Topical lidocaine reduces the risk of perioperative airway complications in children with upper respiratory tract infections

Abstract: Purpose To determine the effect of topically applied lidocaine on perioperative airway complications when using a laryngeal mask airway device (LMAD) in children either with or without a history of recent or ongoing upper respiratory tract infection (URI). Methods In a randomized controlled double-blind trial, 34 children with a history of recent or ongoing URI and 32 non-URI children-all of whom were younger than age ten and scheduled to undergo minor surgical procedureswere randomly assigned to either a lido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
1
25
1
1
Order By: Relevance
“…There were three studies that reported mixed data for laryngospasm, stridor and bronchospasm . Adverse effects of lidocaine were not reported in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were three studies that reported mixed data for laryngospasm, stridor and bronchospasm . Adverse effects of lidocaine were not reported in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…). Of the included studies, eight were available in English and one in Spanish . Eight studies were presented as peer‐reviewed papers and one as an unpublished abstract .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both these studies looked exclusively at the incidence of postextubation laryngospasm in patients undergoing tonsillectomy and adenoidectomy, a cohort of patients who are likely to be at increased risk of laryngospasm. The other three studies (19)(20)(21) found no difference in the incidence of laryngospasm following topicalization. As laryngospasm is a relatively rare occurrence in the general pediatric population, these studies may have been underpowered to detect a difference.…”
Section: Perioperative Respiratory Adverse Eventsmentioning
confidence: 92%